A Systematic Review of Affective Factors on Locating Specialized Hospitals - Mehrinejad Khotbehsara, Elham; Safari, Hossein (Salehan Institute of Higher Education, 2018)
Considering the importance of ways and accessibility in today's busy life, choosing the right place is one of the necessities of each project. It is worth saying that the sensitivity of the patient's condition and related issues has made the hospital locating more important and also it must be noted the different dimensions of health or disease affect each other and is influenced by each other. Indeed, data analysis suggests that the goal of designing a therapeutic centres should not only be included of physical therapy of individuals but in addition to the provision of health services, providing mental and psychological needs of users is one of the most basic design goals of such places. Therefore the hospital locating is taking place in Rasht led to a tree diagram for hospital locating factors based on a summary of scientists and researchers backgrounds which corresponding analysis was made by analysing the selected site and numbering matrixes based on tree diagram. The results of the matrix with an average of 1.31 out of 2 indicate that the selected field is suitable to construct a hospital from locating perspective.